Dosimetric Characterization of the Dual Layer MLC System for an O-Ring Linear Accelerator. (8th November 2019) - Kim, Michele M.; Bollinger, Douglas; Kennedy, Chris; Zou, Wei; Scheuermann, Ryan; Teo, Boon-Keng Kevin; Metz, James M.; Dong, Lei; Li, Taoran
The Halcyon is Varian's latest linear accelerator that offers a single 6X flattening-filter-free beam with a jawless design that features a new dual layer multileaf collimator system with faster speed and reduced transmission. Dosimetric characteristics of the dual layer multileaf collimator system including transmission, dosimetric leaf gap, and tongue and groove effects were measured. Ionization chambers, diode arrays, and an electronic portal imaging device were used to measure various multileaf collimator characteristics. Transmission through both multileaf collimator banks was found to be 0.008%, while the distal and proximal banks alone had transmission values of 0.4%. The penumbra was slightly sharper for fields using only the distal multileaf collimator bank but found to be largely independent of leaf position with values between 2.7 to 3.0 mm at dmax for the combined multileaf collimator banks. The dosimetric leaf gap was measured for the proximal and distal multileaf collimator banks both individually and together and found to have values of −0.216 mm, −0.225 mm, and 0.964 mm, respectively. Measurements of dosimetric leaf gap at the leaf edge and midline were also performed. Tongue and groove effects were investigated with both the electronic portal imaging device and a 2-dimensional array of diodes.